Autophagy mediates bronchial cell malignant transformation induced by chronic arsenic exposure via MEK/ERK1/2 pathway. (10th October 2020) - Wu, Linqing; Wang, Zengbin; Li, Xiaotong; He, Xiaoli; Han, Yanfei; Chen, Yizhong; Liu, Liangying; Fu, Lengxi; Zhang, Tao
Highlights: Chronic arsenic exposure of human bronchial epithelial BEAS-2B cells induces EMT. The malignant transformation is mediated via activation of MEK/ERK1/2 signaling. Inhibition of autophagy further promotes EMT and generation of inflammasomes. These suggest an important role of autophagy in arsenic-induced lung tumorigenesis. Abstract: Chronic exposure to arsenic increases the risk of developing a variety of human cancers including lung carcinomas. However, the exact molecular mechanism underlying arsenic carcinogenicity remains largely unknown. Autophagy is a conserved catabolic process for maintaining cellular protein homeostasis whose defects might result in accumulation of dysfunctional organelles and damaged proteins thus promoting tumorigenesis. In the present study, we found that chronic exposure of human bronchial epithelial BEAS-2B cells to sub-lethal dose of sodium arsenite led to autophagy activation and induced an epithelial-to-mesenchymal transition (EMT) to enhance cell migratory and invasive capability. The malignant transformation was mediated via activation of MEK/ERK1/2 signaling. Importantly, inhibition of autophagy in these arsenic-exposed cells by pharmacological intervention or genetic deletion further promoted the EMT and increased the generation of inflammasomes. Both autophagy inhibitor and genetic deletion of autophagy core gene Beclin-1 produced similar effects. These results may suggest the important role of autophagy in sodium arsenite-induced lung tumorigenesis which may serve as a potential target in prevention and treatment of arsenic-imposed lung cancer.